Synthesis, thermal behaviors, and energetic properties of asymmetrically substituted tetrazine-based energetic materials - Wang, Shenghui; Chen, Xiang; Chen, Yuankai; Nan, Hai; Li, Yuanyuan; Ma, Haixia (Frontiers in Chemistry, 2022)
1,2,4,5-tetrazine ring is a common structure for the construction of energy-containing compounds, and its high nitrogen content and large conjugation effect give it the advantage of a good balance between energy and mechanical stability as a high-nitrogen energy-containing material. However, most of the reported works about tetrazine energetic materials (EMs) are symmetrically substituted tetrazines due to their easy accessibility. A small number of reports show that asymmetrically substituted tetrazines also have good properties, such as high density and generation of enthalpy and energy. Herein, two asymmetrically substituted tetrazines and their five energetic salts were prepared and fully characterized by IR spectroscopy, NMR spectra, elemental analysis, and differential scanning calorimetry (DSC). The structure of the two compounds was further confirmed by single-crystal X-ray diffraction studies. The thermal behaviors and thermodynamic parameters were determined and calculated. In addition, the energetic properties and impact sensitivities of all the compounds were obtained to assess their application potential. The results show that compounds 2–4 and 7–9 show higher detonation velocities than TNT, and the hydrazinium salt 9 possesses the best detonation properties (D = 8,232 m s−1 and p = 23.6 GPa). Except for 4 and 3, all the other compounds are insensitive, which may be applied as insensitive explosives. Noncovalent interaction analysis was further carried out, and the result shows that the strong and high proportion of hydrogen bonds may contribute to the low-impact sensitivity.